Professional BlazeDS : creating rich Internet applications with Flex and Java - Tiwari, Shashank (Wrox professional guides., 2009)
A hands-on guide to creating Rich Internet Applications (RIA) using BlazeDS BlazeDS enables you to easily connect to back-end distributed data and push data in real time to Adobe Flex and Adobe AIR applications in order to garner more responsive Rich Internet Application (RIA) experiences. It is a scalable option for Flex and Java integration and allows you to create excellent RIAs with both Flex and Java. This informative resource provides you with detailed examples and walkthroughs that explain the best practices for creating RIAs using BlazeDS. You'll begin with the essentials of BlazeD.